Performance analysis in Chinese female club soccer based on offensive and defensive technical-tactical indicators - Xing, Y.; Erdmann, W.; Chamera, T. (Polish Journal of Sport and Tourism, 2024)
Introduction. This study aimed to analyze how technical and tactical performance indicators differ by different match outcomes in women`s soccer and apply a comprehensive approach to match analysis.